2015
DOI: 10.1007/s13277-015-4071-1
|View full text |Cite
|
Sign up to set email alerts
|

miR-383 inhibits hepatocellular carcinoma cell proliferation via targeting APRIL

Abstract: Mounting evidence has shown that microRNAs (miRNAs), a class of small non-coding RNAs, are frequently deregulated in human malignancies and have pivotal roles in diverse biological processes including cancer cell proliferation. Herein, we investigated the expression pattern of miR-383 in 64 hepatocellular carcinoma (HCC) tissues and 4 HCC cell lines and found that miR-383 was downregulated in HCC tissues and cell lines. Moreover, miR-383 expression in HCC was significantly correlated with tumor size and tumor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 29 publications
1
65
1
Order By: Relevance
“…In gastric cancer miR-23b associated with unfavorable survival [52]. The existing evidence from miR-383 suggests its tumor-suppressing role in vitro, for example, hepatocellular, pancreatic, and esophageal carcinomas [5355]. This is in contradiction with our results, which suggested both miR-23b and miR-383 act clearly oncogenic in Hodgkin lymphomas.…”
Section: Discussioncontrasting
confidence: 99%
“…In gastric cancer miR-23b associated with unfavorable survival [52]. The existing evidence from miR-383 suggests its tumor-suppressing role in vitro, for example, hepatocellular, pancreatic, and esophageal carcinomas [5355]. This is in contradiction with our results, which suggested both miR-23b and miR-383 act clearly oncogenic in Hodgkin lymphomas.…”
Section: Discussioncontrasting
confidence: 99%
“…It has also been revealed by the recent studies that low levels of miR-383 were correlated with high levels of APRIL expression in clinical HCC samples. 16 Overall, the conclusions obtained from the recent studies show that miR-383 has a critical role in cell cycle regulation, proliferation, and apoptosis in cancer. However, its functional and regulatory roles in all human cancers have not been clearly elucidated yet.…”
Section: Capability Of Mir-383 To Function As a Colorectal Cancer Tummentioning
confidence: 96%
“…This miRNA has been found to be down regulated in testicular embryonic carcinoma, hepatocellular carcinoma, glioma, medulloblastoma, 15,16 breast cancer, 17 and ependymoma. 18 Results of a study showed that exposure to UV led to a significantly lower expression of miR-383 in A431cells (a model human cell line of epidermoid carcinoma).…”
Section: Introductionmentioning
confidence: 99%
“…The target mRNA molecules are then silenced by one or more of the following processes: cleavage of the mRNA strand into two pieces, destabilization of the mRNA through shortening of its polyA tail, and preventing translation of mRNA into protein [9,10]. As important regulatory molecules, miRNAs are involved in multiple cellular processes, including development [11][12][13], proliferation [14][15][16][17], migration [16,[18][19][20], and apoptosis [17,21,22]. Studies have demonstrated that miRNAs are linked with various cancers and tumors in humans [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%